2018
DOI: 10.1177/0049475517752205
|View full text |Cite
|
Sign up to set email alerts
|

Chronic urinary carrier state due to Salmonella Typhi causing urinary tract infection in an immunocompetent healthy woman

Abstract: Enteric fever caused by Salmonella Typhi is a global public health problem. With adequate treatment, most patients recover from the acute phase; however, 2-4% develop a chronic carrier state acting as reservoir of infection by continued shedding of bacteria in faeces and urine. Recovery of S. Typhi from urine is rare, even in endemic areas. The three main causes of bacteriuria arise following a recent episode of typhoid fever, in chronic carrier states involving the urinary system and occasionally following lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Regarding the associated factors of typhoid fever; washing with soap, history of typhoid fever, history of previous hospitalization, and having a chronic underlying disease were identified as potential factors of typhoid fever (P < 0.05). After initial treatment, patients with typhoid fever may become an asymptomatic carriers of Salmonella, and continue to shade bacteria in their stool and urine, which can be a source of reinfection 39,40 or reactivation of previous infections 7 . This could be the possible reason why the history of typhoid fever and previous history of hospitalization was found significantly associated with typhoid fever (P < 0.05) in the current study as in Bahir Dar, Ethiopia 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the associated factors of typhoid fever; washing with soap, history of typhoid fever, history of previous hospitalization, and having a chronic underlying disease were identified as potential factors of typhoid fever (P < 0.05). After initial treatment, patients with typhoid fever may become an asymptomatic carriers of Salmonella, and continue to shade bacteria in their stool and urine, which can be a source of reinfection 39,40 or reactivation of previous infections 7 . This could be the possible reason why the history of typhoid fever and previous history of hospitalization was found significantly associated with typhoid fever (P < 0.05) in the current study as in Bahir Dar, Ethiopia 7 .…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[7][8][9] As a result, Salmonella bacteriuria must be a proxy marker for an underlying risk factor, such as genitourinary abnormalities. However, cases have been reported in immunocompetent individuals as well 3,10 and occur via hematogenous spread from gastroenteritis or direct urethral fecal contamination. A case-control study by Yeung et al has also indicated cystoscopy as a risk factor; the authors report 11 patients with Salmonella bacteriuria, of whom eight had undergone cystoscopy preceding bacteriuria.…”
Section: Discussionmentioning
confidence: 99%
“…were also isolated. 28,29,32 In addition to immunocompromised patients and those with chronic diseases, urinary tract abnormalities, such as lithiasis and fistulas, are related to urinary disease by nontyphoidal serotypes. 28 In parallel, it has also been discussed that the occurrence of a chronic carrier state enhances the access to the urinary system, relapse, and release in the environment.…”
Section: Usa 56mentioning
confidence: 99%
“…28 In parallel, it has also been discussed that the occurrence of a chronic carrier state enhances the access to the urinary system, relapse, and release in the environment. 29,32 Other examples include Salmonella Gallinarum in renal transplant recipient; 30 Salmonella Stanleyville after an episode of gastroenteritis; 30 and Salmonella Typhi associated with urolithiasis and identified in urine after a recent episode of typhoid fever, suggesting poor sanitary. In addition, a few documented cases propose an association of the urinary tract infection with sexually acquired Haemophilus quentini.…”
Section: Usa 56mentioning
confidence: 99%